Development of Canva Based E-Book “AKMULBAT” (Noble Morals with Friends) in PAI Learning for Grade VI - Wulandari, Dita Dwi; Marlina, Rini; Hovipah, Sri; Aeni, Ani Nur (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2025)
This study aims to develop a Canva-based interactive e-book entitled “AKMULBAT” (Noble Morals with Friends) to improve the understanding of grade VI elementary school students about the importance of respecting differences of opinion in Islamic Religious Education. Differences of opinion in elementary schools are often a challenge, so educational efforts are needed that foster mutual respect and are in line with Islamic teachings. This research uses the Design and Development (D&D) method using the ADDIE research model (Analysis, Design, Development, Implementation, and Evaluation). The AKMULBAT interactive e-book integrates interactive elements such as video analysis, question and answer games, and evaluation so that it becomes an attractive learning media for students. The development process includes identifying the learning outcomes of Merdeka Curriculum, plotting, and creating content using Canva, Capcut, Runway, Heyzine, and Wordwall. The pilot test at SDN Gudangkopi I on March 12, 2025, with 12 grade VI students, involved expert validation from media experts and material experts, along with student feedback through a likert scale, which showed positive results. The results showed increased student motivation and improved understanding of appreciating differences. The interactivity of the e-book effectively engages students, in line with findings on interactive learning. The novelty lies in the innovative integration of various technologies to provide an accessible, engaging and effective learning resource, which can be accessed through laptops and projectors. The media is expected to encourage students creativity, in line with the evolving times.